Workshop Pemanfaatan Kahoot dalam Pembelajaran Matematika di Sekolah - Zulfah; Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Learning innovations that utilize technology are an important need in efforts to improve the quality of education. This study aims to identify the effectiveness of the Kahoot utilization workshop in mathematics learning in schools. This workshop was designed to improve teachers' skills in using Kahoot as an interactive and interesting technology-based learning tool. This study used 4 stages, namely planning/preparation, implementation, observation and evaluation, and reflection. The research method involved the participation of mathematics teachers from various schools who attended training sessions, direct practice, and teaching simulations. The results showed that the workshop succeeded in improving teachers' understanding of Kahoot's features and their ability to develop lesson plans involving the platform. Teachers were also able to design contextual quizzes that were relevant to mathematics material, thus motivating students to learn actively and increasing their involvement in the learning process. It was concluded that this workshop had a positive impact on the quality of mathematics learning through the use of educational technology. This study recommends regular training, exploration of other technologies, and the provision of an offline version of Kahoot to support wider implementation, especially in areas with limited internet access.